Perancangan Sistem Pengelolaan Parkir Otomatis Menggunakan NodeMCU dan Sensor Infrared (Studi Kasus di Area Parkir PT Inovasi Cell) - Iis Torisa Utami; Riri Irawati; Ririt Roeswidiah; Bruri Trya Sartana; Fahmi Syahriza (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The purpose of this research focuses on the utilization of a NodeMCU ESP8266 microcontroller using the Arduino IDE and infrared sensors for an automatic parking barrier management system. The research method used is a literature study, along with several materials and tools that support the design of the automatic parking barrier management system, such as a system-on-a-chip (SoC) based on the ESP8266 developed by Espressif Systems, which includes components like the CPU, RAM, and internet connectivity. Based on the test results, the design of the automatic control system effectively improves convenience and security for parking users. Users can utilize parking facilities more easily, quickly, and efficiently. This is due to the capability of the automatic gate system to optimally detect the presence of a vehicle at a distance of approximately ±2 cm within a duration of 8 seconds. In addition, the infrared sensor works synergistically with the ultrasonic sensor to provide signals or commands to the servo motor for automatically opening and closing the parking barrier. The barrier closes within approximately ±2 seconds after a vehicle is detected entering the parking area, and likewise opens when a vehicle exits the area. The success of this system is also greatly influenced by good management practices, including regular calibration, security system integration, monitoring, operational efficiency, digital data management, and the implementation of sustainability principles. Therefore, through well-planned and systematic management supported by technological development, the automatic parking barrier system can enhance user comfort, security, and service efficiency. Overall, the design of this system can serve as an effective solution to support modern parking facilities that are efficient, integrated, and focused on customer satisfaction.